SISTEM PAKAR TES KEPRIBADIAN PAPI KOSTICK UNTUK SELEKSI DAN PENEMPATAN TENAGA KERJA - Cemani, Dwi Puri; Soebroto, Arief Andy; Wicaksono, Satrio Agung (MATICS, 2013)
Company commonly in doing the  selection or the placement of the employees by using curriculum vitae (CV) or application form to see the applicant’s ability. The weakness, although the CV writer who is capable who is able until the level of  interview is not a guarantee that he is the right person who is needed by the company. The company can see the adjustment between the aplicant with the working through personality test. Kostick PAPI method is implemented in the expert system to evaluate behavioral and individuals working way in the relation to the working situation. The expert system is implemented in a web-based. The testing used are validation testing (Black Box testing) and accuracy testing the of expert systems. The result of Black Box testing   is 100% showing of  functionality system works well as requirements list. The result of accuracy testing is 96,49% showing of an expert system functions well as Kostick PAPI method.